2017
DOI: 10.1073/pnas.1708319114
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an O-mannosylation pathway selectively serving cadherins and protocadherins

Abstract: The cadherin (cdh) superfamily of adhesion molecules carry O-linked mannose (O-Man) glycans at highly conserved sites localized to specific β-strands of their extracellular cdh (EC) domains. These O-Man glycans do not appear to be elongated like O-Man glycans found on α-dystroglycan (α-DG), and we recently demonstrated that initiation of cdh/protocadherin (pcdh) O-Man glycosylation is not dependent on the evolutionary conserved POMT1/POMT2 enzymes that initiate O-Man glycosylation on α-DG. Here, we used a CRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 45 publications
15
115
0
Order By: Relevance
“…Whereas N ‐glycosylations are found in many human proteins, there are currently only some human proteins known, which carry O ‐mannosylations at specific serine or threonine residues. However, in the last decade it was shown that especially members of the cadherin family carry O ‐mannosylations . Remarkably, Larsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas N ‐glycosylations are found in many human proteins, there are currently only some human proteins known, which carry O ‐mannosylations at specific serine or threonine residues. However, in the last decade it was shown that especially members of the cadherin family carry O ‐mannosylations . Remarkably, Larsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…TMTC1-4 are not only implicated in the O-mannosylation of cadherins but were also found to be involved in the O-mannosylation of several ER/Golgi resident proteins, including ERp57, ERdj4 and FKBP10 (Larsen et al, 2017a). Each of these are important chaperones for protein folding of the secretory pathway aiding in disulfide bond formation, BiP activation and proline cis trans isomerization.…”
Section: Discussionmentioning
confidence: 99%
“…TMTC1-4 were discovered to contribute to the O-mannosylation proteome when a subset of substrates remained O-mannosylated in cells that lacked the known Omannosyltransferases, POMT1 and POMT2 (Larsen et al, 2017a(Larsen et al, , 2017b. A significant difference in O-mannosylation of the cadherin family of proteins was observed upon knockout of all four TMTCs in HEK293 cells (HEK293 SC/TMTC1,2,3,4 ) (Larsen et al, 2017a). Glycoproteomics was used to determine that E-cadherin was O-mannosylated at nine sites (Supplemental Fig.…”
Section: Tmtc3 Rescues O-mannosylation Of E-cadherinmentioning
confidence: 99%
See 2 more Smart Citations